2019
DOI: 10.31235/osf.io/2g7yd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Double-Edged Sword of Banning Extremists from Social Media

Abstract: Over the past few years, researchers, activists, and policymakers have engaged in debates over how social media companies should respond to extremism on their platforms. One facet of this debate focuses on the consequences – online and offline – of different approaches. Debates about the effectiveness of various approaches have not recognized that there are two different goals: reducing extremist violence and reducing extremism. This article presents a thought experiment that unpacks these goals, thinks throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Research of Twitter networks [12] has shown that there is segregation that exists in the partisan networks, with the separation becoming quite evident in retweet networks with minimal connectivity between left-and right-leaning users. There are studies to reduce polarisation [19,27,44]. Stasavage et al [44] explains how public group discussion can help to reduce polarisation but this does not happen when representatives from different factions are involved.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research of Twitter networks [12] has shown that there is segregation that exists in the partisan networks, with the separation becoming quite evident in retweet networks with minimal connectivity between left-and right-leaning users. There are studies to reduce polarisation [19,27,44]. Stasavage et al [44] explains how public group discussion can help to reduce polarisation but this does not happen when representatives from different factions are involved.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Stasavage et al [44] explains how public group discussion can help to reduce polarisation but this does not happen when representatives from different factions are involved. Jackson et al [27] studied that particular users can be removed from the network participation to reduce polarization. A study by Garimella et al [19] addresses the problem of reducing polarisation by adding edges in the graph of users that produce the most significant reduction in the polarisation.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Existe literatura sobre los enfoques que pueden adoptarse para reducir la polarización en las redes sociales [16]- [20]; sin embargo, hay desafíos que aparecen comúnmente. Estos están relacionados con que los enfoques requieren interpretación humana en cuanto a qué direcciones tomar al comprender la motivación de la audiencia [21], que el contenido es visible para la inspección [22] o que los usuarios particulares pueden ser eliminados de la participación en la red [22]. El documento [23] discute cómo el debate grupal público puede proporcionar un medio para reducir la polarización, pero esto puede no tener lugar cuando lo hacen representantes de facciones opuestas.…”
Section: Palabras Claveunclassified
“…Durante las discusiones no polarizadas, o con las estrategias de inoculación vigentes, los usuarios que influyen en el nivel inferior pueden «superponerse» y, durante la «polarización», la intimidación juega un papel importante. La dinámica de polarización no se ve afectada o abordada directamente, ya que esto puede introducir complicaciones imprevistas e inducir posibles efectos contrarios a los esperados durante los intercambios agitados [22].…”
Section: Debateunclassified
“…We delineate two types of interventions to mitigate the spread of extremist views. Negative interventions aim to subtract attention from the opinion ecosystem by placing fact-check warnings on postings [26], shadowbanning [42] or outright banning extremist social media groups and accounts [20]. While negative interventions are effective [6], they are available solely to the social media platforms who tend to use them sparsely [28].…”
Section: Introductionmentioning
confidence: 99%